L'èxtasi poètic de Fontanella: metateatre i música a la Lloa per la Tragicomèdia pastoral d'amor, firmesa i porfia. - GILABERT, GASTON (Scripta, 2018)
In the absence of monographic studies on Fontanella's Lloa, this paper analyses its dramatic structure, starting with a reflection on their classification within the genre and on the context of 17th century Barcelona where it could have been staged. The functional importance that this Barcelonian poet grants to music and metatheatre leads to an interpretation of the Lloa from a poetic-musical point of view, which allows a new reading of certain passages and a critical evaluation that affects not only the piece in question, but also the whole Tragicomèdia pastoral d'amor, firmesa i porfia and the avant-garde character of the Catalan theatre of the Modern Age.